Display and interface design subtle science, exact art - Bennett, Kevin B. 1957- (CRC Press, 2011)
"Technological advances in hardware and software provide powerful tools with the potential to design interfaces that are powerful and easy to use. Yet, the frustrations and convoluted "work-arounds" often encountered make it clear that there is substantial room for improvement. Drawn from more than 60 years of combined experience studying, implementing, and teaching about performance in human-technology systems, Display and Interface Design: Subtle Science, Exact Art provides a theoretically-based yet practical guide for ecological display and interface design.Written from the perspective of cognitive systems engineering and ecological interface design, the book delineates how to design interfaces tailored to specific work demands, leverage the powerful perception-action skills of the human, and use powerful interface technologies wisely. This triadic approach (domain, human, interface) to display and interface design stands in sharp contrast to traditional dyadic (human, interface) approaches. The authors describe general principles and specific strategies at length and include concrete examples and extensive design tutorials that illustrate quite clearly how these principles and strategies can be applied. The coverage spans the entire continuum of interfaces that might need to be developed in today's work places. The book includes access to a web site containing examples of the dynamic properties of displays.The reason that good interfaces are few and far between is really quite simple: they are extremely difficult to design and build properly. While there are many books available that address display design, most of them focus on aesthetic principles but lack scientific rigor, or are descriptive but not prescriptive. Whether you are exploring the principles of interface design or designing and implementing interfaces, this book elucidates an overarching framework for design that can be applied to the broad spectrum of existing domains"--